Pengembangan Modul Berbasis Research untuk Meningkatkan Pemahaman Konsep dan Kemampuan Metakognisi Siswa Kelas X pada Topik Ekosistem Di SMA Negeri 1 Karanganyar Tahun Pelajaran 2013/2014 - Wahyu Fitri Lestari; Sri Widoretno; Nurmiyati Nurmiyati (BIO-PEDAGOGI, 2014)
The research and development are aimed: a) to develop a module based on research to improve the concept understanding and metacognitive ability of X student’s grade on the topic of ecosystem, b) to know the feasibility of module based on research to improve the concept understanding and metacognitive ability of X student’s grade on the topic of ecosystem, c) to know the effectiveness of module based on research to improve the concept understanding and metacognitive ability of X student’s grade on the topic of ecosystem. The research and development use  Borg and Gall ‘s procedure modified into seven stages, namely: 1) research and initial data collection, includes a review of literature and analysis the requirement; 2) Planning, involves making matrix of module, elaboration the indicators and learning objectives; 3) Preparation of the initial product; 4) First field testing, includes the validation test by expert of materials, expert of module design, expert of module developer and grammar, and expert of cognitive test, as well as user module (teachers and students); 5) Initial product revision; 6) The operasional field testing (stage II) with quasy experiment method. Test the effectiveness of product using Anacova at significans 0,05; 7) Final product revision. The result of the research shows that the module based on research on the topic of ecosystem is developed according to the Borg and Gall’s procedure modified into seven stages and arranged based on the research component. The feasibility of the module based on research is declared qualified "worthy" by the expert of materials, expert of module developer and grammar, expert of module design, and students (small groups), as well as qualified "very feasible" by expert of developer for test evaluation and the teacher (education practitioner). The module based on research is effective to improve the concept understanding represented by the average value of posstest for the treatment grade higher than the grade control, although statistical analysis shows no significant differences (Fvalue = 0,007 <Ftable (0,05:1; 58) = 4,00). The module based on research is effective to improve the metacognitive ability as indicated by the average value of posstest for treatment grade higher than the grade control, as well as statistical analysis shows a significant difference (Fvalue = 6,390> Ftable (0,05:1; 58) = 4,00). The conclusion of the research is the module based on research on the topic of ecosystem is feasible in learning and effective to improve the concept understanding and metacognitive ability. Key Words: Module Based on Research, Concept Understanding,Metacognitive Ability